Women's agency and rituals in mixed and female Masonic orders - Heidle, Alexandra; Snoek, Joannes A. M. (Aries book series 1871-1405, 2008)
Women have been structurally part of the masonic enterprise from at least the middle of the 18th century. This volume focuses on two aspects: Women's agency (the power women gained and exercised in this context) and rituals (the role of men and women in changing and shaping the rituals women work with)